BUILDING RESEARCH CAPACITY IN HIGHER EDUCATION: PERCEPTIONS OF FACULTY WORKING IN A STATE UNIVERSITY IN KYRGYZSTAN - Shamshieva, Rakhat (Nazarbayev University Graduate School of Education, 2022)
The role of research has been essential in disseminating knowledge and advancement of universities. In this essence, research capacity at universities is a solid instrument to equip the faculty members with necessary research tools. In order to conduct research, faculty members need enough capacities such as analytical skills and academic writing skills and may position research as a complex process to stay motivated and positive consistently (Altbach, 2014; Ridley,2011). Within the Kyrgyzstani educational system, the teaching faculty, as part of their qualifications, are required to earn an academic degree to increase the quality of research and university rank (MoES, 2015). In effect, the official ordinance of the president of the Kyrgyz Republic is to introduce Ph.D. programs at universities and increase high-impact publications (MOES, 2021). The present study aimed to explore the faculty’s perceptions of research capacity at the one university in Kyrgyzstan. Semi-structured interviews were addressed to 10 faculty members with academic degrees. The findings suggest that many university teachers display a low motivation to conduct research due to the teaching load, low salary, gender norms, and publishing challenges in higher education institutions. Research opportunities are hampered by a lack of internal and external financial support. There is a dearth of scholarly activities to improve research and academic writing skills. The findings revealed that research standards present in the international curricula are not widely used at this university. Keywords: research capacity, higher education, publishing, research opportunities
Keywords: research capacity; higher education; publishing; research opportunities; Type of access: Open Access; Research Subject Categories::SOCIAL SCIENCES